The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1968
DOI: 10.3109/17453676808989436
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in the Upper Limb During Tourniquet Ischaemia:A Clinical Study

Abstract: View related articles Citing articles: 28 View citing articles I'ro1n the Cliiiir for 0rtllop:irtlics and l'raiimattrlogg, llrncl : Profcssor I<. 15. I(allio, and the Chilclrrii's Clinic, Hrad : IBrofrssor Niilo Hallmaii, of tlic lliiivrrsity Crntral Hospital, Hclsiiilti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Caldwell previously showed in isolated muscle preparations that sonic muscle tissue fatigue sets in at pH 7.0 and rigor follows at pH 6.0 . The Wilgis results complement a similar study by Solonen and colleagues in Finland in which they histologically depicted capillary and cell damage in striated muscle caused by ischemia up to 2 hours. They demonstrated that the pH decreased enough to indicate that ischemia of longer than 2 hours using a tourniquet may be approaching these critical points.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Caldwell previously showed in isolated muscle preparations that sonic muscle tissue fatigue sets in at pH 7.0 and rigor follows at pH 6.0 . The Wilgis results complement a similar study by Solonen and colleagues in Finland in which they histologically depicted capillary and cell damage in striated muscle caused by ischemia up to 2 hours. They demonstrated that the pH decreased enough to indicate that ischemia of longer than 2 hours using a tourniquet may be approaching these critical points.…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, measurements have been made on venous blood withdrawn during and after the use of pneumatic tourniquets. 5,7,8,29,30 These investigations were based on the premise that chemical .001, BTA vs 10 minutes 20 minutes 7.08 AE 80.09 (6.89-7.31) .001, 10 minutes vs 20 minutes 30 minutes 6.91 AE 0.12 (6.63-7.25) .001, 20 minutes vs 30 minutes 40 minutes 6.76 AE 0.12 (6.50-6.99)…”
Section: Discussionmentioning
confidence: 99%
“…Marked hypertensive responses ( > 30%) in the present study were seen only in the general anaesthesia patients (8/15). The balanced anaesthesia including enflurane inhalation at or above 1 MAC concentration (7) was unable to prevent a hypertensive response in the majority of patients. In a retrospective analysis of 724 patients with a tourniquet and undergoing orthopaedic surgery under different types of anaesthesia, approximately 64% of the balanced anaesthesia patients had an increase in arterial blood pressure exceed-ing 30% anaesthesia, in contrast to approximately 2% during spinal anaesthesia (unpublished observation).…”
Section: Haemodynamic Changesmentioning
confidence: 92%
“…The acute interruption of blood flow causes metabolic disorders which could be of importance in the pathogenesis of tourniquet injuries. The ef fects of tourniquet ischemia on acid-base balance in the arm [2,18], and short-term [5] and 2-hour [7] ischemia in the leg have been investigated in man. Studies on animals have been carried out by several authors [2,5], Metabolic disturbances have also been investigated during reconstruc tive arterial surgery [6,8,14,17].…”
Section: /L Ew Is/l üJedahl/lôfstrômmentioning
confidence: 99%